Effects of structural heterogeneity of nanostructured copper on the evolution of the sizes of recrystallized grains during annealing. Issue 1 (July 2015) - Lin, F X; Zhang, Y B; Pantleon, W; Jensen, D Juul
Abstract: Recrystallization in copper deformed by dynamic plastic deformation was investigated using electron backscatter diffraction. The recrystallized grains show a broad size distribution. The kinetics of grains of different sizes is observed to be different: In the beginning of recrystallization, the area fraction of small recrystallized grains increases rapidly. At later stages of recrystallization, the area fraction of small recrystallized grains is stable, while the area fractions of medium and large recrystallized grains increase. Correlation between the broad grain size distribution (and its evolution) and the heterogeneous deformed microstructure is discussed.